2019
DOI: 10.2147/ott.s213421
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knockdown of ROS proto-oncogene 1 inhibits migration and invasion in gastric cancer cells by targeting the PI3K/Akt signaling pathway</p>

Abstract: Objectives: Gastric cancer ranks the fourth most common cancer and the third leading cause of cancer mortality in the world. ROS proto-oncogene 1 (ROS1) is an oncogene and ROS1 rearrangement has been reported in many cancers. Our study aimed to investigate the potential function and the precise mechanisms of ROS1 in gastric cancer. Methods: In our study, the analysis of ROS1 expression and clinical pathologic factors of gastric cancer in gastric cancer using TCGA database demonstrated that ROS1 expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…39 And it is also found that the migration and invasion of GC cells are attenuated by inhibiting the PI3K/AKT signaling pathway. 40 In addition, PI3K/AKT signaling pathway can also affect EMT. For example, breast cancer 1 (AIB1) enhances EMT by activating PI3K/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…39 And it is also found that the migration and invasion of GC cells are attenuated by inhibiting the PI3K/AKT signaling pathway. 40 In addition, PI3K/AKT signaling pathway can also affect EMT. For example, breast cancer 1 (AIB1) enhances EMT by activating PI3K/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the numbers of invaded cells decreased after treatment with ethyl acetate extract of H. hirsute in dose dependent manner. Metastasis is a complex process, which is related to multiple intracellular signals such as production of reactive oxygen species (ROS) [29,30], and contribution of microRNAs (miRNAs) [31,32]. These changes elevate EMT, leading to increases in migration and invasion of cancer cells [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The function of the PI3K/AKT signaling pathway is significantly correlated with the BAG4-induced EMT and the expression of ZEB1 [ 61 ]. Meanwhile, silencing ROS1 , an oncogene that encodes a tyrosine kinase of the insulin receptor family, attenuated GC cell invasion and EMT through the PI3K/Akt signaling pathway [ 62 ]. Carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6), a glycosylphosphatidylinositol-linked immunoglobulin superfamily member, has pivotal oncogenic roles by inducing EMT as validated by upregulations in the EMT markers N-cadherin, Vimentin, and Slug.…”
Section: Signaling Pathways Involved In Gc Invasion and Metastasismentioning
confidence: 99%